Overall profiles of the res judicata in the Brazilian Civil Procedual Law - Zufelato, Camilo (2016)
The purpose of this paper is offer to the reader, especially to the foreign reader, an overall picture of the res judicata en the Brazilian civil procedural law, with a special approach (not the only one) in the treatment to this topic by the Procedual Civil Code of 2015. The first part analyses a set of situaciones, quite peculiar actually, of the own authority of the res judicata along its shades; then, secondly, treats classical themes of the objective and subjective limits, and the peculiar regimen of the collective actions of the res judicata. Finally, the main is to analyze the overall profiles of the institute, without stopping in controversies or specifications regarding the perspective of the domestic law.